Vulnerability, family assets, and income-generating strategies of households in rural Mexico. Issue 5 (19th October 2020) - Fierros-González, Isael; Mora-Rivera, Jorge; Avila-Foucat, Véronique Sophie
ABSTRACT: This study is a first step in analyzing, on a national scale in Mexico, the assets, income and vulnerability context of households in rural communities. A multinomial logit model was used to show the impact of family labor, education, indigenous status, climate change, and access to markets on the probability of belonging to the different categories of households with diverse sustainable livelihoods. Our results provide evidence that increasing investment in human capital encourages participation by large numbers of households in the productive activities that offer the greatest returns. The findings also suggest that public policies should aim to solve structural concerns that limit the efficacy of the use of assets to promote sustainable development in rural communities in countries like Mexico.